Tönnis and the Novel IHDI Radiographic Classification Systems for the Developmental Dysplasia of The Hip (DDH): Evaluation of 406 hips with DDH - Topal, M.; Yilar, S. (Universa BV, 2023)
In this study, we aimed to compare the efficiency of Tönnis and the novel International Hip Dysplasia Institute (IHDI) in decision making and in presuming the outcomes in children who had undergone closed reduction and casting. 406 hips of 298 patients who had undergone closed reduction and spica casting were included in this retrospective study. All hips were classified according to Tönnis and IHDI systems. Bucholz-Ogden classification was used for avascular necrosis. The outcomes of patients for each classification system were compared, in terms of the presence of avascular necrosis, redislocations and secondary surgeries at the end of the follow-up period. 318 hips were evaluated as Tönnis grade 2 dysplasia. 24 had avascular necrosis, 9 had redislocations. 79 hips were evaluated as Tönnis grade 3 dysplasia. 18 had AVN, 7 had redislocations. 9 hips were evaluated as Tönnis grade 4 dysplasia 3 had AVN, 4 had redislocations. 203 patients were evaluated as IHDI grade 2 dysplasia. 7 had AVN, 7 had redislocations.185 patients were assessed as IHDI grade 3 dysplasia. 33 had AVN, 11 had redislocations. 18 patients were evaluated as IHDI grade 4 dysplasia. 5 had AVN, 6 had redislocations. Both Tönnis classification and IHDI classification systems are reliable and efficient systems for evaluating the severity and predicting the success of closed reduction and casting for the treatment of DDH. IHDI classification has certain benefits, such as being a practical classification and a better distribution within the groups.
Keywords: Treatment Outcome; Osteonecrosis; Humans; Infant; Developmental Dysplasia of the Hip; Orthopedic Procedures; Child; Hip Dislocation, Congenital; Retrospective Studies; 3. Good health